Studi Perkembangan Aerenkim Akar Padi Sawah dan Padi Ladang pada Tahap Persemaian dengan Perlakuan Perendaman - Fitri Handayani; Tesri Maideliza; - Mansyurdin (Jurnal Biologi Universitas Andalas, 2013)
The study of root aerenchyma development of wetland paddy cv."anak daro" and upland paddy cv. "merah" at nursery stageby flooding treatment was conducted from January to April 2013 in green house and Laboratory of Plant Development and Structure, Biology Departement, Andalas University, Padang. The objective of this study was to observe the aerechyma development in the root cortex and its zone along root. The root of paddy as materials were prepared by the paraffin method. The result showed that aerenchyma was developed from cortical cells of proximal root either in wetland or upland paddy in two days after seedling. At 8 days after seedling, wetland paddy with flooding treatment formed 27-29 aerenchymatous cavities compared to 27-28 cavities of their control. Upland paddy with flooding treatment formed 28-30 aerenchymatous cavities and did not form any cavity on their control.. The aerenchyma of both paddies developed completely between outer and inner cortex in 14 days after seedling. The aerenchymatous zone was developed completely from proximal up to distal root at 21 days after seedling.Keywords: wetland paddy, upland paddy, flooding, aerenchyma development, root